Lithium secondary battery
The lithium secondary battery design, featuring a lithium transition metal oxide positive electrode and a phosphonium salt-based ionic liquid in the non-aqueous electrolyte, addresses temperature-related performance issues by enhancing stability and reducing resistance and gas generation.
Patent Information
- Application Number
- JP2024558437
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-04-11
- Filing Date
- 2023-04-12
- Publication Date
- 2025-04-15
AI Technical Summary
Lithium secondary batteries face challenges in maintaining performance at high and low temperatures due to issues with solvent volatility, gas generation, and electrode stability.
A lithium secondary battery design incorporating a positive electrode with a lithium transition metal oxide and a non-aqueous electrolyte containing a phosphonium salt-based ionic liquid, which enhances flame retardancy and suppresses side reactions.
The battery achieves improved high-temperature storage characteristics and low-temperature storage characteristics, reducing gas generation and resistance, while maintaining capacity and cycle stability.
Smart Images

Figure 2025511349000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0045380 filed on April 12, 2022 and Korean Patent Application No. 10-2023-0047808 filed on April 11, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated as part of this specification.
[0002] The present invention relates to a lithium secondary battery that exhibits excellent high-temperature storage characteristics and low-temperature storage characteristics. [Background technology]
[0003] In modern society, dependence on electrical energy is increasing, which is leading to an increase in the amount of electrical energy produced. In order to solve the environmental problems that have arisen during this process, new renewable energy power generation has been attracting attention as a next-generation power generation system.
[0004] On the other hand, new renewable energy sources require large-capacity power storage devices to ensure a stable supply of power. Lithium-ion batteries are currently in the spotlight as the devices with the highest energy density available commercially.
[0005] The lithium ion battery is roughly composed of a positive electrode made of a transition metal oxide containing lithium, a negative electrode capable of storing lithium, a non-aqueous electrolyte solution that serves as a medium for transferring lithium ions, and a separator.
[0006] In particular, non-aqueous electrolytes are known to be components that affect the stability and safety of batteries, and much research is being conducted on them.
[0007] In general, non-aqueous electrolytes have mainly been used as liquid electrolytes in which electrolyte salts are dissolved in organic solvents. However, such liquid electrolytes have the disadvantage that, under high-temperature atmospheres, the organic solvent is highly volatile, a large amount of gas is generated by side reactions with the electrodes, and the stability is low due to combustion caused by the temperature rise of the battery itself. In addition, under low-temperature atmospheres, the resistance at the interface between the electrodes and the non-aqueous electrolyte increases, resulting in various performance degradation.
[0008] Therefore, there is a demand for the development of a lithium secondary battery with a new configuration that can prevent deterioration of the secondary battery in high-temperature and low-temperature atmospheres and improve various performances. Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention is intended to solve the above problems, and provides a lithium secondary battery having improved high-temperature storage characteristics and low-temperature storage characteristics. [Means for solving the problem]
[0010] In order to achieve the above object, in one embodiment of the present invention, A positive electrode containing a lithium transition metal oxide represented by the following formula 1 as a positive electrode active material; a negative electrode including a negative electrode active material; a separator interposed between the positive electrode and the negative electrode; a non-aqueous electrolyte solution including a lithium salt, a non-aqueous organic solvent, and an additive; The additive provides a lithium secondary battery comprising an ionic liquid represented by the following Chemical Formula 2:
[0011] [Chemical formula 1] Li 1+a Ni x Co y M 1 z M 2 w O2 In the above Chemical Formula 1, M 1is Mn, Al, or a combination thereof; M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, Mg, Ca and Sr, and 0≦a≦0.5, 0.5 <x<1.0、0<y≦0.4、0<z≦0.4、0≦w≦0.1である。
[0012] [ka] In the above Chemical Formula 2, R is an alkylene group having 1 to 5 carbon atoms; n is an integer from 0 to 3. Effect of the Invention
[0013] The lithium secondary battery according to the present invention uses a positive electrode containing, as a positive electrode active material, a lithium transition metal oxide with a nickel content of more than 50 mol %, in combination with a nonaqueous electrolyte solution containing a phosphonium salt-based ionic liquid as an additive, thereby forming a stable coating with low resistance and high flame retardancy on the electrode surface and preventing deterioration of the battery, thereby achieving excellent high-temperature storage characteristics and low-temperature storage characteristics.
[0014] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the above-mentioned content of the invention, serve to further understand the technical concept of the present invention. Therefore, the present invention should not be interpreted as being limited only to the matters described in such drawings. [Brief description of the drawings]
[0015] [Figure 1] 1 is a graph showing the evaluation results of the amount of gas generated after high-temperature storage of a lithium secondary battery according to Experimental Example 2 of the present invention. [Diagram 2] 1 is a graph showing the evaluation results of low-temperature cycle characteristics of a lithium secondary battery according to Experimental Example 3 of the present invention. [Diagram 3] 11 is a graph showing the evaluation results of low-temperature storage characteristics of a lithium secondary battery according to Experimental Example 4 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will now be described in more detail.
[0017] The terms and words used in the description of the present invention and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0018] For example, in this specification, "%" means % by weight unless expressly indicated otherwise.
[0019] In addition, in this specification, unless otherwise defined, the term "substituted" means that at least one hydrogen bonded to a carbon atom is replaced with an element other than hydrogen, for example, by an alkyl group having 1 to 5 carbon atoms or a fluorine element.
[0020] As a result of extensive research into improving the resistance and output characteristics of lithium secondary batteries, the inventors have discovered that by combining a positive electrode containing a positive electrode active material of a specific composition with a non-aqueous electrolyte containing an additive of a specific structure, it is possible to suppress an increase in resistance at low temperatures, improve the flame retardancy and ignition possibility of a lithium secondary battery in a high-temperature storage atmosphere, and thereby improve high-temperature storage characteristics, thereby completing the present invention.
[0021] The present invention will be specifically described below.
[0022] Lithium secondary battery According to one embodiment of the present invention, the lithium secondary battery of the present invention comprises: A positive electrode containing a lithium transition metal oxide represented by the following formula 1 as a positive electrode active material; a negative electrode including a negative electrode active material; a separator interposed between the positive electrode and the negative electrode; a non-aqueous electrolyte solution including a lithium salt, a non-aqueous organic solvent, and an additive; The additive may include an ionic liquid represented by the following formula 2:
[0023] [Chemical formula 1] Li 1+a Ni x Co y M 1 z M 2 w O2 In the above Chemical Formula 1, M 1 is Mn, Al, or a combination thereof; M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, Mg, Ca and Sr, and 0≦a≦0.5, 0.5 <x<1.0、0<y≦0.4、0<z≦0.4、0≦w≦0.1である。
[0024] [ka] In the above Chemical Formula 2, R is an alkylene group having 1 to 5 carbon atoms; n is an integer from 0 to 3.
[0025] Hereinafter, each component of the lithium secondary battery according to the present invention will be described in more detail.
[0026] (1) Positive electrode The positive electrode according to the present invention may include a positive electrode active material layer containing a positive electrode active material, and if necessary, the positive electrode active material layer may further include a conductive material and / or a binder.
[0027] The positive electrode active material may include a lithium transition metal oxide represented by the following Chemical Formula 1:
[0028] [Chemical formula 1] Li 1+a Ni x Co y M 1 z M 2 wO2 In the above chemical formula 1, M 1 is Mn, Al, or a combination thereof, M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, Mg, Ca, and Sr, and 0 ≦ a ≦ 0.5, 0.5 < x < 1.0, 0 < y ≦ 0.4, 0 < z ≦ 0.4, 0 ≦ w ≦ 0.1.
[0029] The above 1 + a represents the atomic fraction of lithium in the lithium transition metal oxide, and 0 ≦ a ≦ 0.5, preferably 0 ≦ a ≦ 0.2, more preferably 0 ≦ a ≦ 0.1 may be applicable.
[0030] The above x represents the atomic fraction of nickel among all the transition metal elements in the lithium transition metal oxide, and 0.6 ≦ x ≦ 1.0, specifically 0.75 ≦ x ≦ 0.98 may be applicable, and it is more advantageous for realizing high capacity that the nickel content is 0.5 or more.
[0031] The above y represents the atomic fraction of cobalt among all the transition metal elements in the lithium transition metal oxide, and 0 < y ≦ 0.4, specifically 0 < y ≦ 0.3, more specifically 0.05 ≦ y ≦ 0.3 may be applicable.
[0032] The above z represents the atomic fraction of the M 1 element among all the transition metal elements in the lithium transition metal oxide, and 0 < z ≦ 0.4, preferably 0 < z ≦ 0.3, more preferably 0.01 ≦ z ≦ 0.3 may be applicable.
[0033] The above w represents the atomic fraction of the M 2 element among all the transition metal elements in the lithium transition metal oxide, and 0 < w ≦ 0.1, preferably 0 < w ≦ 0.05, more preferably 0 < w ≦ 0.02.
[0034] Specifically, in order to realize a high-capacity battery, the cathode active material has a Ni content of 0.55 atm% or more, Li(Ni 0.6 Mn 0.2 Co 0.2)O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.7 Mn 0.2 Co 0.1 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, Li(Ni 0.86 Mn 0.07 Co 0.05 Al 0.02 )O2, Li(Ni 0.90 Mn 0.05 Co 0.05 The positive electrode active material may contain a lithium composite transition metal oxide such as Li(Ni)O2 in order to realize a high capacity battery. 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.7 Mn 0.2 Co 0.1 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, Li(Ni 0.86 Mn 0.07 Co 0.05 Al 0.02 )O2, Li(Ni 0.90 Mn 0.05 Co 0.05 It is preferable that the lithium composite transition metal oxide includes a lithium composite transition metal oxide such as 02.
[0035] On the one hand, in the positive electrode active material, as the content of nickel among all transition metal elements in the lithium transition metal oxide increases, it becomes easier to realize a high-capacity battery. However, when the nickel content is 70 atm% or more, due to structural instability, various nucleophilic reactions occur on the surface of the positive electrode, and as a result, during high-temperature storage, the carbonate solvent is likely to decompose, increasing the generation of gases such as CO2. The gas induced in this way causes a side reaction of continuously forming Li2CO3, LiF, etc. by binding with Li ions on the surfaces of the positive electrode and the negative electrode. Such side reactions are the cause of the increased resistance of the lithium secondary battery. Therefore, in the present invention, as described later, by using in combination a non-aqueous electrolyte containing an additive capable of suppressing the side reaction of the carbonate solvent, it is possible to effectively suppress the increase in resistance of a lithium secondary battery including a positive electrode active material with a nickel content of 70 atm% or more.
[0036] On the other hand, the positive electrode active material of the present invention is a lithium composite metal oxide represented by the above chemical formula 1, combined with a lithium-manganese-based oxide (for example, LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (for example, LiCoO2, etc.), a lithium-nickel-based oxide (for example, LiNiO2, etc.), a lithium-nickel-manganese-based oxide (for example, LiNi 1-Y Mn Y O2 (0 < Y < 1), LiMn 2-Z Ni Z O4 (0 < Z < 2)), a lithium-nickel-cobalt-based oxide (for example, LiNi 1-Y1 Co Y1 O2 (0 < Y1 < 1)), a lithium-manganese-cobalt-based oxide (for example, LiCo 1-Y2 Mn Y2 O2 (0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (0 < Z1 < 2), or Li(Ni p1 Co q1 Mn r2 )O4 (0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2)), etc. can also be used in combination.
[0037] The positive electrode active material may be contained in an amount of 80% by weight to 99% by weight, specifically 90% by weight to 99% by weight, based on the total weight of the solid content of the positive electrode slurry. If the content of the positive electrode active material is 80% by weight or less, the energy density is reduced and the capacity is decreased.
[0038] Next, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not undergo chemical changes in the battery that is constructed and has electronic conductivity.Specific examples include carbon powders such as carbon black, acetylene black (or denka black), ketjen black, channel black, furnace black, lamp black, and thermal black, graphite powders such as natural graphite with a highly developed crystal structure, artificial graphite, and graphite, conductive fibers such as carbon fibers and metal fibers, conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive materials such as polyphenylene derivatives, and one or more of these can be used alone or in mixture.
[0039] The conductive material may be contained in an amount of 0.1% by weight to 10% by weight, preferably 0.1% by weight to 5.0% by weight, based on the total weight of the positive electrode active material layer.
[0040] Secondly, the binder serves to enhance adhesion between particles of the positive electrode active material and between the positive electrode active material and the current collector.
[0041] Examples of such binders include fluororesin-based binders including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE), rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber, cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose, polyalcohol-based binders including polyvinyl alcohol, polyolefin-based binders including polyethylene and polypropylene, polyimide-based binders, polyester-based binders, and silane-based binders, which may be used alone or in combination of two or more.
[0042] The binder may be contained in an amount of 0.1% by weight to 15% by weight, preferably 0.1% by weight to 10% by weight, based on the total weight of the positive electrode active material layer.
[0043] Such a positive electrode of the present invention can be manufactured by a method known in the art for manufacturing a positive electrode. For example, the positive electrode can be manufactured by a method of dissolving or dispersing a positive electrode active material, a binder, and / or a conductive material in a solvent to prepare a positive electrode slurry, which is then coated on a positive electrode current collector, and then dried and rolled to form an active material layer, or a method of casting the positive electrode slurry on another support, and then peeling off the support to obtain a film, which is then laminated on a positive electrode current collector.
[0044] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has electrical conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. The positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive strength of the positive electrode material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0045] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of them may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it can be adjusted to an appropriate viscosity of the positive electrode mixture in consideration of the coating thickness of the positive electrode mixture, production yield, workability, etc.
[0046] (2) Negative electrode Next, the negative electrode will be described.
[0047] The negative electrode according to the present invention includes a negative electrode active material layer containing a negative electrode active material, and the negative electrode active material layer may further include a conductive material and / or a binder, if necessary.
[0048] The negative electrode active material may be any of various negative electrode active materials used in the art, such as a carbon-based negative electrode active material, a silicon-based negative electrode active material, or a mixture thereof.
[0049] According to one embodiment, the negative electrode active material may include a carbon-based negative electrode active material, and the carbon-based negative electrode active material may be any of various carbon-based negative electrode active materials used in the art, such as graphite-based materials such as natural graphite, artificial graphite, and Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes, soft carbon, hard carbon, etc. The shape of the carbon-based negative electrode active material is not particularly limited, and materials of various shapes such as amorphous, plate-like, flaky, spherical, and fibrous shapes may be used.
[0050] Preferably, the negative electrode active material can be at least one carbon-based negative electrode active material selected from natural graphite and artificial graphite. Both natural graphite and artificial graphite can be used together to increase the adhesive strength with the current collector and suppress detachment of the active material.
[0051] According to another embodiment, the negative electrode active material may be a combination of the carbon-based negative electrode active material and the silicon-based negative electrode active material.
[0052] The silicon-based negative electrode active material is, for example, metal silicon (Si), silicon oxide (SiO x, where 0 < x < 2), may contain one or more selected from the group consisting of silicon carbide (SiC) and Si-Y alloy (wherein Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si). As the element Y, it can be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db (dubnium), Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0053] Since the silicon-based negative electrode active material exhibits higher capacity characteristics than the carbon-based negative electrode active material, when the silicon-based negative electrode active material is further included, more excellent capacity characteristics can be obtained. However, in the case of a negative electrode containing a silicon-based negative electrode active material, the SEI film contains more oxygen (O)-rich components in the SEI film compared to a graphite negative electrode, and the SEI film containing O-rich components tends to decompose more easily when Lewis acids such as HF and PF5 are present in the electrolytic solution. Therefore, in the case of a negative electrode containing a silicon-based negative electrode active material, in order to maintain a stable SEI film, it is necessary to suppress the generation of Lewis acids such as HF and PF5 in the electrolytic solution or remove (or scavenge) the generated Lewis acids. The non-aqueous electrolytic solution according to the present invention contains an electrolytic solution additive capable of forming a stable film on the positive electrode and the negative electrode, so that the decomposition of the SEI film can be effectively suppressed when using a negative electrode containing a silicon-based active material.
[0054] On the other hand, the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material may be 3:97 to 99:1, preferably 5:95 to 15:85 by weight ratio. When the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material satisfies the above range, while improving the capacity characteristics, the volume expansion of the silicon-based negative electrode active material can be suppressed, and excellent cycle performance can be ensured.
[0055] The negative electrode active material may be contained in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer. When the content of the negative electrode active material satisfies the above range, excellent capacity characteristics and electrochemical characteristics can be obtained.
[0056] Furthermore, as the negative electrode active material, a thin film of metallic lithium or a titanium composite oxide (LTO) can be used as necessary.
[0057] Next, the conductive material may be included to further improve the conductivity of the negative electrode active material layer, and is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity. For example, the conductive material may be carbon powder such as carbon black, acetylene black (or denka black), ketjen black, channel black, furnace black, lamp black, thermal black, etc., graphite powder such as natural graphite with a highly developed crystal structure, artificial graphite, graphite, etc., conductive fibers such as carbon fibers and metal fibers, conductive powders such as carbon fluoride powder, aluminum powder, nickel powder, etc., conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, conductive materials such as polyphenylene derivatives, etc. The conductive material may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer.
[0058] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and examples of the binder include fluororesin-based binders including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE), rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber, cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose, polyalcohol-based binders including polyvinyl alcohol, polyolefin-based binders including polyethylene and polypropylene, polyimide-based binders, polyester-based binders, and silane-based binders.
[0059] The binder may be contained in an amount of usually 0.1% by weight to 15% by weight, preferably 0.1% by weight to 10% by weight, based on the total weight of the negative electrode active material layer.
[0060] The negative electrode can be manufactured by a method for manufacturing a negative electrode known in the art. For example, the negative electrode can be manufactured by applying a negative electrode slurry, which is manufactured by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material in a solvent, onto a negative electrode current collector, and rolling and drying the slurry to form an active material layer, or by casting the negative electrode slurry onto another support, peeling off the support, and laminating the resulting film onto the negative electrode current collector.
[0061] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, aluminum-cadmium alloy, etc. can be used. The negative electrode current collector may usually have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0062] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of them may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it can be adjusted to an appropriate viscosity of the negative electrode slurry in consideration of the coating thickness of the negative electrode mixture, production yield, workability, etc.
[0063] (3) Separator The separator included in the lithium secondary battery of the present invention may be a commonly used ordinary porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in a laminate thereof, or an ordinary porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, but is not limited thereto.
[0064] (4) Non-aqueous electrolyte The lithium secondary battery according to the present invention may include a non-aqueous electrolyte solution including a lithium salt, a non-aqueous organic solvent, and an additive, and the additive may include an ionic liquid represented by the following Chemical Formula 2:
[0065] [ka] In the above Chemical Formula 1, R is an alkylene group having 1 to 5 carbon atoms; n is an integer from 0 to 3.
[0066] (4-1) Lithium salt First, the lithium salt will be described below.
[0067] The lithium salt may be any salt commonly used in non-aqueous electrolytes for lithium secondary batteries. For example, the cation may be Li + The anion is F. - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO4 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3- , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CF3(CF2)7SO3 - and SCN - may include at least one selected from the group consisting of:
[0068] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 The lithium salt may include a single substance or a mixture of two or more substances selected from the group consisting of LiAlCl4, LiAlO4, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(pentafluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2, and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2). In addition to the above-mentioned lithium salts, lithium salts that are commonly used in electrolytes for lithium secondary batteries may be used without limitation. Specifically, the lithium salt may include LiPF6.
[0069] The lithium salt can be appropriately changed within a range that is normally usable, but in order to obtain an optimal effect of forming a coating for preventing corrosion of the electrode surface, it may be contained in the electrolyte at a concentration of 0.8 M to 3.0 M, specifically, at a concentration of 1.0 M to 3.0 M. When the concentration of the lithium salt satisfies the above range, the viscosity of the nonaqueous electrolyte can be controlled to realize optimal impregnation, and the mobility of lithium ions can be improved, thereby obtaining an effect of improving the capacity characteristics and cycle characteristics of the lithium secondary battery.
[0070] (4-2) Nonaqueous organic solvent The non-aqueous organic solvent will be described below.
[0071] As the non-aqueous organic solvent, various organic solvents commonly used in non-aqueous electrolytes can be used without limitation, and there is no limitation on the type of the organic solvent as long as it can minimize decomposition due to oxidation reaction during the charge / discharge process of the secondary battery and can exhibit the desired properties together with the additives.
[0072] Specifically, the non-aqueous organic solvent may include a cyclic carbonate organic solvent, a chain carbonate organic solvent, a chain ester organic solvent, or a mixed organic solvent thereof.
[0073] The cyclic carbonate organic solvent is a high-viscosity organic solvent that has a high dielectric constant and therefore easily dissociates a lithium salt in a non-aqueous electrolyte solution. Specific examples of the cyclic carbonate organic solvent include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and in particular, ethylene carbonate.
[0074] The chain carbonate organic solvent is an organic solvent having low viscosity and low dielectric constant, and specific examples thereof may include at least one organic solvent selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and specifically may include ethyl methyl carbonate (EMC).
[0075] The chain ester organic solvent is a solvent that is relatively more stable at high temperatures and high voltages than cyclic carbonate organic solvents, and can improve the drawback of cyclic carbonate organic solvents that cause gas generation during high voltage operation, while also achieving high ionic conductivity.
[0076] Specific examples of the chain ester organic solvent include at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate, and specifically, at least one of ethyl propionate and propyl propionate.
[0077] Furthermore, the nonaqueous electrolyte solution of the present invention may further contain a cyclic ester-based organic solvent, if necessary.
[0078] The cyclic ester organic solvent may contain at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0079] Meanwhile, in the non-aqueous electrolyte solution of the present invention, the remainder other than the lithium salt and the compound represented by Formula 1 as an additive may be a non-aqueous organic solvent unless otherwise specified.
[0080] (4-3) Ionic liquid represented by chemical formula 2 The nonaqueous electrolyte for a lithium secondary battery of the present invention may contain an ionic liquid represented by the following chemical formula 2 as an additive.
[0081] [ka] In the above Chemical Formula 2, R is an alkylene group having 1 to 5 carbon atoms; n is an integer from 0 to 3.
[0082] Specifically, the ionic liquid represented by the above formula 2 contains a phosphonium cation in its structure, and has a lower binding strength with a non-aqueous organic solvent than an ionic liquid containing a nitrogen cation that has been used as an additive in the past. Therefore, when lithium ions dissolved in a non-aqueous organic solvent are intercalated into a negative electrode, particularly a negative electrode containing a carbon-based negative electrode active material, during charging, the lithium ions are easily intercalated, and the penetration of the ionic liquid is suppressed, preventing exfoliation of the negative electrode surface, thereby making it possible to manufacture a lithium secondary battery with improved charge / discharge efficiency and battery energy density. In addition, the phosphonium salt-based ionic liquid represented by the above formula 2 forms an inorganic coating on the surface of the positive electrode, thereby preventing a decrease in resistance and a side reaction between the electrode and the non-aqueous electrolyte. In particular, the phosphonium salt-based ionic liquid represented by the above chemical formula 2 can suppress the decomposition of the carbonate solvent during high-temperature storage by partially bonding the phosphonium cation with the carbonate solvent, thereby reducing the generation of gases such as CO2 on the surface of the positive electrode and / or negative electrode, thereby suppressing the generation of by-products caused by the bonding of gases such as CO2 with Li ions. This can effectively improve problems such as an increase in the resistance of the lithium secondary battery during high-temperature storage. Such effects can be more effectively achieved in lithium secondary batteries containing a positive electrode active material with a nickel content of 70 atm% or more.
[0083] Specifically, in the above chemical formula 2, R may be an alkylene group having 1 to 3 carbon atoms.
[0084] More specifically, the ionic liquid represented by the above chemical formula 2 may be at least one of the compounds represented by the following chemical formulas 2-1 to 2-3.
[0085] [ka]
[0086] [ka]
[0087] [ka]
[0088] The ionic liquid represented by the above chemical formula 2 may be contained in an amount of 0.3% by weight to 50% by weight based on the total weight of the nonaqueous electrolyte solution.
[0089] When the content of the ionic liquid represented by Chemical Formula 2 satisfies the above range, a stable passive film with low resistance is formed on the surfaces of the positive and negative electrodes, and safe high and low temperature capacity characteristics are ensured, and an enhanced flame retardancy effect is realized, thereby further improving the performance of the lithium secondary battery under high and low temperature atmospheres.
[0090] Specifically, the ionic liquid represented by the above chemical formula 2 may be contained in an amount of 0.5% by weight to 30% by weight, and preferably 0.5% by weight to 20% by weight, based on the total weight of the nonaqueous electrolyte solution.
[0091] (4-4) Other additives Meanwhile, the non-aqueous electrolyte of the present invention may further contain other additives to prevent the non-aqueous electrolyte from decomposing and causing the collapse of the negative electrode in a high-output environment, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, prevention of overcharging, and effect of suppressing battery expansion at high temperatures.
[0092] Examples of such other additives include at least one selected from the group consisting of cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based or phosphite-based compounds, borate-based compounds, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.
[0093] Examples of the cyclic carbonate compounds include vinylene carbonate (VC) and vinyl ethylene carbonate (VEC).
[0094] The halogen-substituted carbonate compounds include fluoroethylene carbonate (FEC).
[0095] The sultone compound may be, for example, at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.
[0096] The sulfate compound may be, for example, ethylene sulfate (Esa), trimethylene sulfate (TMS), methyl trimethylene sulfate (MTMS), or the like.
[0097] The phosphate- or phosphite-based compound may be, for example, one or more compounds selected from the group consisting of lithium difluoro(bisoxalate)phosphate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.
[0098] Examples of the borate-based compound include tetraphenylborate, lithium oxalyl difluoroborate (LiODFB) capable of forming a coating on the surface of the negative electrode, and lithium bisoxalate borate (LiB(C2O4)2, LiBOB).
[0099] The benzene-based compound may be fluorobenzene or the like, the amine-based compound may be triethanolamine, ethylenediamine or the like, and the silane-based compound may be tetravinylsilane or the like.
[0100] The lithium salt-based compound is a compound different from the lithium salt contained in the non-aqueous electrolyte solution, and may be one or more compounds selected from the group consisting of LiPO2F2, LiODFB, LiBOB (lithium bis(oxalato)borate (LiB(C2O4)2) and LiBF4.
[0101] Among such other additives, in order to form a stronger SEI coating on the surface of the negative electrode during the initial activation step, other additives having excellent coating formation effect on the surface of the negative electrode, specifically, one or more selected from the group consisting of vinylene carbonate, vinyl ethylene carbonate, fluoroethylene carbonate (FEC) and lithium oxalyl difluoroborate (LiODFB), may be included.
[0102] Meanwhile, the other additives may be used in combination of two or more kinds, and may be contained in an amount of 50% by weight or less, specifically 0.01% by weight to 10% by weight, preferably 0.05% by weight to 5.0% by weight, based on the total weight of the non-aqueous electrolyte. If the content of the other additives is less than 0.01% by weight, the effect of improving the low-temperature output of the battery, as well as the high-temperature storage characteristics and high-temperature life characteristics is weak, and if the content of the other additives is more than 50% by weight, excessive side reactions may occur in the electrolyte during charging and discharging of the battery. In particular, if the SEI film forming additive is added in an excessive amount, it may not be sufficiently decomposed at high temperatures, and may remain unreacted or precipitated in the electrolyte at room temperature. As a result, side reactions that reduce the life or resistance characteristics of the secondary battery may occur.
[0103] Meanwhile, the lithium secondary battery of the present invention may be manufactured and applied by a conventional method known in the art. Specifically, an electrode assembly in which a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode are sequentially laminated is formed, and the electrode assembly is housed in a battery case, and then the nonaqueous electrolyte of the present invention is introduced to manufacture the lithium secondary battery.
[0104] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0105] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the present invention. However, the examples according to the present invention can be modified into various other forms, and the scope of the present invention should not be construed as being limited to the examples detailed below. The examples of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. EXAMPLES
[0106] [Example] Example 1. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:70 to a concentration of 1.0M, and then 1.0 wt% of the compound represented by the above formula 2-1 and 0.5 wt% of vinylene carbonate as an additive were added to prepare a non-aqueous electrolyte.
[0107] (Secondary battery manufacturing) N-methyl-2-pyrrolidone (NMP) is used as the positive electrode active material (Li(Ni 0.6 Mn 0.2 Co 0.2 A positive electrode slurry (solid content: 50 wt%) was prepared by adding 100% ethylenediaminetetraacetate (Et2O2), a conductive material (carbon black), and a binder (polyvinylidene fluoride) in a weight ratio of 97.5:1:1.5. The positive electrode slurry was applied to a 12 μm-thick aluminum (Al) thin film, which is a positive electrode current collector, and dried. Then, a roll press was performed to prepare a positive electrode.
[0108] Anode active material (artificial graphite), binder (SBR-CMC) and conductive material (carbon black) were mixed in a weight ratio of 95:3.5:1.5 to water as a solvent to prepare anode slurry (solid content: 60 wt%). The anode slurry was applied to a copper (Cu) thin film as anode current collector with a thickness of 6 μm, dried and then roll pressed to prepare anode.
[0109] The positive electrode, a polyolefin-based porous separator coated with inorganic particles (Al2O3), and a negative electrode were sequentially stacked to prepare an electrode assembly, which was then placed in a pouch-type battery case, and the non-aqueous electrolyte for lithium secondary batteries was injected to prepare a pouch-type lithium secondary battery having a driving voltage of 4.2 V or more.
[0110] Example 2. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:70 to a concentration of 1.0M, and then 30.0 wt% of the compound represented by the above formula 2-1 and 0.5 wt% of vinylene carbonate as an additive were added to prepare a non-aqueous electrolyte.
[0111] (Secondary battery manufacturing) A pouch-type lithium secondary battery was manufactured in the same manner as in Example 1, except that the nonaqueous electrolyte solution prepared above was injected.
[0112] Example 3. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 20:80 to a concentration of 1.2M, and then 0.5 wt% of the compound represented by the above formula 2-1 and 0.5 wt% of vinylene carbonate and 0.5 wt% of 1,3-propane sultone as other additives were added to prepare a non-aqueous electrolyte.
[0113] (Secondary battery manufacturing) N-methyl-2-pyrrolidone (NMP) is used as the positive electrode active material (Li(Ni 0.6 Mn 0.2 Co 0.2 A positive electrode slurry (solid content: 50 wt%) was prepared by adding 100% ethylenediaminetetraacetate (Et2O2), a conductive material (carbon black), and a binder (polyvinylidene fluoride) in a weight ratio of 97.5:1:1.5. The positive electrode slurry was applied to a 12 μm-thick aluminum (Al) thin film, which is a positive electrode current collector, and dried. Then, a roll press was performed to prepare a positive electrode.
[0114] Anode active material (artificial graphite), binder (SBR-CMC) and conductive material (carbon black) were mixed in a weight ratio of 95:3.5:1.5 to water as a solvent to prepare anode slurry (solid content: 60 wt%). The anode slurry was applied to a copper (Cu) thin film as anode current collector with a thickness of 6 μm, dried and then roll pressed to prepare anode.
[0115] The positive electrode, a polyolefin-based porous separator coated with inorganic particles (Al2O3), and a negative electrode were sequentially stacked to prepare an electrode assembly, which was then placed in a pouch-type battery case, and the non-aqueous electrolyte for lithium secondary batteries was injected to prepare a pouch-type lithium secondary battery having a driving voltage of 4.2 V or more.
[0116] Example 4. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 20:80 to a concentration of 1.2M, and then 0.5 wt% of the compound represented by the above formula 2-1 and 0.5 wt% of vinylene carbonate and 0.5 wt% of 1,3-propane sultone as other additives were added to prepare a non-aqueous electrolyte.
[0117] (Secondary battery manufacturing) N-methyl-2-pyrrolidone (NMP) is used as the positive electrode active material (Li(Ni 0.86 Mn 0.07 Co 0.05 Al 0.02 A positive electrode slurry (solid content: 50 wt%) was prepared by adding 100% ethylenediaminetetraacetate (Et2O2), a conductive material (carbon black), and a binder (polyvinylidene fluoride) in a weight ratio of 97.5:1:1.5. The positive electrode slurry was applied to a 12 μm-thick aluminum (Al) thin film, which is a positive electrode current collector, and dried. Then, a roll press was performed to prepare a positive electrode.
[0118] Anode active material (artificial graphite), binder (SBR-CMC) and conductive material (carbon black) were mixed in a weight ratio of 95:3.5:1.5 to water as a solvent to prepare anode slurry (solid content: 60 wt%). The anode slurry was applied to a copper (Cu) thin film as anode current collector with a thickness of 6 μm, dried and then roll pressed to prepare anode.
[0119] The positive electrode, a polyolefin-based porous separator coated with inorganic particles (Al2O3), and a negative electrode were sequentially stacked to prepare an electrode assembly, which was then placed in a pouch-type battery case, and the non-aqueous electrolyte for lithium secondary batteries was injected to prepare a pouch-type lithium secondary battery having a driving voltage of 4.2 V or more.
[0120] Comparative Example 1 A nonaqueous electrolyte for a lithium secondary battery and a pouch-type lithium secondary battery containing the same were manufactured in the same manner as in Example 1, except that LiPF6 was dissolved to a concentration of 1.0 M in a nonaqueous organic solvent prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:70, and 0.5 wt % of vinylene carbonate was added to prepare a nonaqueous electrolyte.
[0121] Comparative Example 2 A non-aqueous electrolyte for a lithium secondary battery and a pouch-type lithium secondary battery containing the same were manufactured in the same manner as in Example 3, except that LiPF6 was dissolved to a concentration of 1.2 M in a non-aqueous organic solvent prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 20:80, and then 0.5 wt % of vinylene carbonate and 0.5 wt % of 1,3-propane sultone were added as additives to manufacture a non-aqueous electrolyte.
[0122] Comparative Example 3. A non-aqueous electrolyte for a lithium secondary battery and a pouch-type lithium secondary battery containing the same were manufactured in the same manner as in Example 4, except that LiPF6 was dissolved to a concentration of 1.2 M in a non-aqueous organic solvent prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 20:80, and then 0.5 wt % of vinylene carbonate and 0.5 wt % of 1,3-propane sultone were added as additives to manufacture a non-aqueous electrolyte.
[0123] [Experimental Example] Experimental example 1. Evaluation of heat generation The lithium secondary batteries manufactured in Examples 1 and 2 and the lithium secondary battery manufactured in Comparative Example 1 were each fully charged to SOC100% (44.3mAh) under a voltage condition of 4.2V. After that, the temperature was raised from room temperature (25°C) to 300°C, and the heat generation amount inside the lithium secondary battery was measured using an MMC device (Multiple Module Calorimeter, MMC274, manufactured by NETZSCH Co., Ltd.), and the results are shown in Table 1 below.
[0124] [Table 1]
[0125] Referring to Table 1 above, it can be seen that the lithium secondary batteries of Example 1 and Example 2 including the nonaqueous electrolyte of the present invention had a reduced amount of heat generated inside the battery compared to the lithium secondary battery of Comparative Example 1. From these results, it was confirmed that the thermal stability of the lithium secondary battery of the present invention was improved.
[0126] Experimental Example 2: Evaluation of gas generation amount after high temperature storage The lithium secondary batteries prepared in Examples 1 and 2 and the lithium secondary battery prepared in Comparative Example 1 were each charged at room temperature (25° C.) at a constant current / constant voltage condition at a rate of 0.33 C to 4.2 V, and then discharged to a depth of discharge (DOD) of 50% to adjust to an SOC of 50%, and then discharged at a rate of 2.5 C for 10 seconds.
[0127] Thereafter, the batteries were stored in an atmosphere at 60° C. for 16 weeks, and the amount of gas generated (mL) of each lithium secondary battery was measured every two weeks. The results are shown in FIG.
[0128] 1, it can be seen that the lithium secondary batteries of Examples 1 and 2 of the present invention had a reduced amount of gas generation (mL) during high temperature storage compared to the secondary battery of Comparative Example 1.
[0129] Experimental Example 3: Evaluation of low-temperature cycle characteristics The lithium secondary batteries prepared in Example 1 and Example 2 and the lithium secondary battery prepared in Comparative Example 1 were each charged at 15° C. under constant current conditions at a rate of 0.33 C up to 4.2 V, and then charged at a constant voltage of 4.2 V. When the charging current reached 0.275 mA, the charging was terminated. After that, the batteries were left for 10 minutes and discharged at a constant current rate of 0.5 C up to 3.0 V.
[0130] Next, the above charge / discharge process was counted as one cycle, and 200 charge / discharge cycles were performed. At this time, the discharge capacity after the first cycle and the discharge capacity after the 200th cycle were measured using a PNE-0506 charger / discharger (manufacturer: PNE Solution Co., Ltd., 5V, 6A), and the capacity retention rate (%) after 200 cycles relative to the initial capacity was calculated. The results are shown in FIG.
[0131] 2, it can be seen that the lithium secondary batteries of Examples 1 and 2 of the present invention have improved low-temperature cycle characteristics compared to the lithium secondary battery of Comparative Example 1.
[0132] Experimental Example 4. Evaluation of low temperature (-10℃) storage characteristics The lithium secondary batteries prepared in Example 1 and Example 2 and the lithium secondary battery prepared in Comparative Example 1 were each fully charged at a 0.33C rate up to 4.2V under constant current-constant voltage conditions, adjusted to SOC50%, and then discharged for 10 seconds at a 2.5C rate to perform charging and discharging. Then, the initial capacity was measured using a PNE-0506 charger / discharger (manufacturer: PNE Solution Co., Ltd., 5V, 6A).
[0133] After that, the battery was aged at -10°C for 3 hours, and then discharged at a 0.67C rate for 30 seconds. The voltage drop was measured using a PNE-0506 charger / discharger (manufacturer: PNE Solutions Co., Ltd., 5V, 6A), and the results are shown in Figure 3.
[0134] In addition, the batteries were discharged for 30 seconds using the PNE-0506 charger / discharger, and then the capacity of each battery was measured, and the capacity retention rate (%) relative to the initial capacity was calculated and shown in the following Table 2. Here, in the following Table 2, the capacity retention rate (%) of the lithium secondary batteries of Example 1 and Example 2 means a relative rate when the capacity retention rate (%) of the lithium secondary battery of Comparative Example 1 is set to 100%.
[0135] [Table 2]
[0136] 3, it can be seen that the lithium secondary batteries of Examples 1 and 2 of the present invention have an improved voltage drop phenomenon at low temperatures and an improved capacity retention rate (%) compared to the lithium secondary battery of Comparative Example 1. From these results, it is predicted that the lithium secondary batteries of Examples 1 and 2 of the present invention have improved storage characteristics due to reduced resistance during low-temperature storage compared to the lithium secondary battery of Comparative Example 1.
[0137] Experimental Example 5. The secondary batteries manufactured in Example 3 and Example 4 and the secondary batteries manufactured in Comparative Example 2 and Comparative Example 3 were activated at 0.1 C CC, degassed, and then charged at a constant current of 0.04 C to 4.2 V at room temperature (25° C.), and then discharged to 3.0 V under constant current (CC) conditions, which constitutes one charge-discharge cycle. Three cycles were performed.
[0138] Next, the battery was charged at 0.33 C CC up to 4.20 V under constant current-constant voltage (CC-CV) charging conditions at 25°C, and then pulse discharged at a 2.5 C rate under SOC50% conditions, and the voltage drop for 10 seconds was measured to determine the initial resistance value.
[0139] Next, the battery was charged at a constant current of 0.04C to 100% SOC (state of charge), and then stored at high temperature (60°C) for 34 weeks. The battery was then charged at room temperature (25°C) to 50% SOC, and then pulse discharged at a rate of 2.5C to measure the voltage drop for 10 seconds to determine the resistance value after high temperature storage.
[0140] Thereafter, the resistance increase rate (%) relative to the initial resistance was calculated and is shown in the following Table 3. Here, the voltage was measured using a PNE-0506 charger / discharger (manufacturer: PNE Solution Co., Ltd., 5V, 6A).
[0141] [Table 3]
[0142] Referring to Table 3 above, the positive electrode active material is Li(Ni 0.6 Mn 0.2 Co 0.2 In the case of the lithium secondary battery of Example 3, which includes a positive electrode containing Li(Ni)O2 and the nonaqueous electrolyte of the present invention, the resistance increase rate was reduced by about 59% compared to the lithium secondary battery of Comparative Example 2. 0.86 Mn 0.07 Co 0.05 Al 0.02 It can be seen that in the case of the lithium secondary battery of Example 4 including a positive electrode containing O2 and the nonaqueous electrolyte of the present invention, the resistance increase rate was reduced by about 64% compared to the lithium secondary battery of Comparative Example 3. In view of these results, it can be seen that a more effective resistance increase suppression effect can be obtained when a positive electrode including a positive electrode active material with a nickel content of 70 atm% or more is combined with the nonaqueous electrolyte of the present invention.
Claims
1. A positive electrode including a lithium transition metal oxide represented by the following formula 1 as a positive electrode active material; a negative electrode including a negative electrode active material; a separator interposed between the positive electrode and the negative electrode; a non-aqueous electrolyte solution including a lithium salt, a non-aqueous organic solvent, and an additive; The additive contains an ionic liquid represented by the following chemical formula 2: [Chemical formula 1] Li 1+a Ni x Co y M 1 z M 2 w O 2 In the above Chemical Formula 1, M 1 is Mn, Al, or a combination thereof; M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, Mg, Ca, and Sr, and 0≦a≦0.5, 0.5<x<1.0, 0<y≦0.4, 0<z≦0.4, and 0≦w≦0.
1. 【Chemistry 1】 In the above Chemical Formula 2, R is an alkylene group having 1 to 5 carbon atoms; n is an integer from 0 to 3.
2. 2. The lithium secondary battery according to claim 1, wherein, in the above Chemical Formula 1, 0≦a≦0.2, 0.6≦x≦1.0, 0<y≦0.3, 0<z≦0.3, and 0<w≦0.
05.
3. 2. The lithium secondary battery according to claim 1, wherein, in Chemical Formula 1, 0≦a≦0.1, 0.75≦x≦0.98, 0.05≦y≦0.3, 0.01≦z≦0.3, and 0<w≦0.
02.
4. The lithium transition metal oxide is Li(Ni 0.6 Mn 0.2 Co 0.2 ) O 2 , Li(Ni 0.7 Mn 0.15 Co 0.15 ) O 2 , Li(Ni 0.7 Mn 0.2 Co 0.1 ) O 2 , Li(Ni 0.8 Mn 0.1 Co 0.1 ) O 2 , Li(Ni 0.8 Co 0.15 A 0.05 ) O 2 , Li(Ni 0.86 Mn 0.07 Co 0.05 A 0.02 ) O 2 and Li(Ni 0.90 Mn 0.05 Co 0.05 ) O 2 2. The lithium secondary battery according to claim 1, wherein the lithium secondary battery is at least one selected from the group consisting of:
5. 2. The lithium secondary battery according to claim 1, wherein the negative electrode active material comprises a carbon-based negative electrode active material, a silicon-based negative electrode active material, or a mixture thereof.
6. 2. The lithium secondary battery according to claim 1, wherein in the above Chemical Formula 2, R is an alkylene group having 1 to 3 carbon atoms.
7. The lithium secondary battery according to claim 1, wherein the ionic liquid represented by the chemical formula 2 is at least one of the compounds represented by the following chemical formulas 2-1 to 2-3. 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】
8. The lithium secondary battery according to any one of claims 1 to 7, wherein the ionic liquid represented by Chemical Formula 2 is contained in an amount of 0.3 wt% to 50 wt% based on the total weight of the non-aqueous electrolyte.
9. 2. The lithium secondary battery according to claim 1, wherein the ionic liquid represented by Chemical Formula 2 is contained in an amount of 0.5% by weight to 30% by weight based on the total weight of the non-aqueous electrolyte.
10. 2. The lithium secondary battery of claim 1, wherein the non-aqueous electrolyte further comprises at least one other additive selected from the group consisting of cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based or phosphite-based compounds, borate-based compounds, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.
Citation Information
Patent Citations
Organic Phosphonium Salts, a Method for their Preparation, and their Use in Electrochemical Systems
EP2952518A1
Ionic liquid
JP2004043407A
Method for producing phosphonium salt
JP2007514679A
Electrolyte, lithium-ion secondary battery electrolyte solution containing the same, and lithium-ion secondary battery using lithium-ion secondary battery electrolyte solution
JP2008071499A
Electrolyte composition and secondary battery
JP2010225510A